DEVELOPMENT OF ANGKLUNG CRAFT SMALL BUSINESS IN SUKAJAYA VILLAGE, LEMBANG DISTRICT, WEST BANDUNG REGENCY - Patimah, Siti; Fauzy, Teddy Hikmat; Pratiwi, Viona; Mahardika, Dimas (LPM Universitas Pasundan, 2023)
One of the business actors who specializes in angklung crafts which is in Sukajaya village, Lembang District, West Bandung Regency named father Rohim. In running a business, we face various problems, including related ones with equipment Which Already worn so that influence in process production. Besides That Also problem other Which faced related to marketing where business actors experience problems in marketing the product. Business actors also do not keep financial records and for Determining the cost of production is based on estimates so no know exactly profit which he obtained. Implementation methods used to overcome the problems faced by business actors is through training and technical guidance. Training conducted with give lecture And understanding related with marketing And cost production. Bintek What is done is by direct practice and followed by giving understanding until you can finally be independent. Apart from that, we also provided machines to businessmen. As a result of the activity, the provision of machine equipment consisting of a drilling machine and a circular cutting machine has been carried out. And online marketing training has been carried out which is included in training activities carried out jointly in the hall in Cihideung village which is attended by other business actors as a whole. Apart from that, training activities and technical training on simple bookkeeping and calculating the cost of production have also been carried out.